Relationship between knowledge and husband support with the use of long-acting contraceptives at the Bermani Ulu Community Health Centre, Rejang Lebong Regency, Bengkulu Province - Aisah, Nur; Jumita, Jumita; Umami, Desi Aulia (Student Scientific Journal, 2025)
Family planning programme is one of the methods to reduce population growth rate. The purpose of this study was to determine the relationship between knowledge and husband's support with the use of long-acting contraceptives at Puskesmas Bermani Ulu, Rejang Lebong Regency, Bengkulu Province.The design used in this study was an analytical survey with a Cross Sectional design. The population in this study were women of childbearing age at the Bermani Ulu Health Centre, Rejang Lebong Regency in the period January-May 2024, totalling 514 people, the sample in this study was 84 respondents. Sampling was taken by purposive sampling. The results obtained from 84 respondents almost half of the respondents (44%) had less knowledge. Of the 84 respondents, most respondents (53.6%) husbands supported the use of long-term contraception. Of the 84 respondents, most respondents (53.6%) used non MHJP contraception and almost half of the respondents (46.4%) did not use non MHJP contraception. There is a relationship between knowledge and long-term contraceptive use at the Bermani Ulu Community Health Centre, Rejang Lebong Regency, Bengkulu Province. There is a relationship between husband's support and the use of long term contraceptives at Puskesmas Bermani Ulu, Rejang Lebong Regency, Bengkulu Province It is expected to increase public knowledge about long term contraception by increasing health promotion programmes through health education and counselling so that long-term awareness of childbearing age to be willing to use long term contraceptives.